Manufacturing human pluripotent stem cell derived endothelial cells in scalable and cell-friendly microenvironments. (28th November 2018) - Lin, Haishuang; Du, Qian; Li, Qiang; Wang, Ou; Wang, Zhanqi; Elowsky, Christian; Liu, Kan; Zhang, Chi; Chung, Soonkyu; Duan, Bin; Lei, Yuguo
Abstract : Alginate hydrogel tubes are designed for the scalable expansion of human pluripotent stem cells and efficient differentiation into endothelial cells. Abstract : Human pluripotent stem cell derived endothelial cells (hPSC-ECs) are of great value for studying and treating vascular diseases. However, manufacturing high quantity and quality hPSC-ECs with current cell culture technologies remains very challenging. Here, we report a novel method that can manufacture hPSC-ECs in scalable and cell-friendly microenvironments to address this challenge. Using this method, hPSCs are expanded and differentiated into ECs in microscale alginate hydrogel tubes. The hydrogel tubes protect cells from the highly variable hydrodynamic conditions and critical hydrodynamic stresses in the culture vessel and limit the cell mass less than the diffusion limits (of human tissue) to ensure efficient mass transport. The hydrogel tubes provide uniform and friendly microenvironments for cells to grow. This novel design leads to extremely high production efficiency. We showed that hPSC-ECs could be produced in 10 days with high viability (>90%), high purity (>80%) and high yield (∼5.0 × 10 8 cells per mL of microspace). The yield is about 250 times that of the current-state-of-the-art. hPSC-ECs made in these hydrogel tubes had similar in vitro and in vivo functions to hPSC-ECs generated by conventional cell culture methods. This simple, scalable, efficient, defined and cost-effective technology will make hPSC-ECs broadly available and affordable for various biomedical applications.